Increased coagulation Factor VIII (FVIII) replacement in patients with moderate Hemophilia A of non-O blood groups (Research, Society and Development, 2024)
Objective: The present study investigated the association between the ABO blood group and the annual consumption of Coagulation Factor VIII (FVIII) concentrate (IU/kg BW/year) in patients with mild and moderate hemophilia A treated at two reference hemophilia center in Brazil (Pará Blood Center and Unicamp Blood Center) Methods: Plasma levels of the von Willebrand factor antigen (FVW:Ag), ristocetin cofactor (FVW:RCo) and FVIII coagulant (FVIII:C) were performed to investigate the correlation between these variables and the ABO immunophenotypes. Results and Discussion: The FVIII consumption (IU/kg BW/year) compared between moderate hemophilia A patients with blood group O and non-O demonstrated increased FVIII consumption among the patients with blood group non-O (p=0.018). In the analysis of this group, plasma levels of FVW:RCo were statistically higher (p=0.045) in comparison to moderate hemophilia A patients with blood group O. Conclusion: Based on the present findings, the ABO blood group is not only a possible indicator for FVIII pharmacokinetics, but also can influence the moderate hemophilia A bleeding phenotype.